PENGARUH RISIKO INVESTASI, RETURN ON EQUITY (ROE) DAN PROCEEDS TERHADAP UNDERPRICING DENGAN REPUTASI UNDERWRITER SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN NON-KEUANGAN YANG IPO DI BEI PERIODE 2010-2014 - Dea Haska; Andewi Rokhmawati; Sjahruddin ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aimed to examine the effects of the investment risk, return on equity (ROE), and proceeds on underpricing and also to test underwriter's reputation as a moderating variable and how its influences the independent variables. The population in this study is a non-financial companies are experiencing underpricing in initial public offering (IPO) at the Indonesian Stock Exchange (IDX) in the period 2010-2014, which amounted to 86 companies. The amount of samples are 73 companies that were taken by using purposive sampling method. The type of data in this research is secondary data, which is the prospectus that published by the company. In terms of data analysis, this study using moderate regression analysis (MRA) with SPSS 21.0. The results of this study showed that: 1) the risk of investment have a negatif influence and significant impact to underpricing with coefficient value 4,606, 2) ROE have a negatif influence and significant impact to underpricing with coefficient value 1,342, 3) proceeds having a negatif significant influences too towards underpricing with coefficient value 4,953. After moderated by underwriter reputation variable, only investment risk and proceeds that have a significant effect on underpricing. For simultaneous effects, all variables are significantly influence the underpricing with 38,8% coefficients determination value.Keyword: underpricing, risk investment, roe, proceeds, underwriter reputation